ANALISIS PENGARUH IKLTh'I ORGANISASI DAN MOTIVASI TERHADAP KEPUASAN KERJADAN KINERJA KARYAWAN (Studi pada PT. Brataco Chemika Cabang Jateng) - Samsul Arifin (Universitas Islam Nahdlatul Ulama Jepara, 2006)
Abstract This Research to test the hypothesis that Organizational Climate and Motivation willinfluence the factor satisfaction Work and Employees Peiformance. this Research Target is to analyze thefactors influencing employees peiformance at PT. Brataco Chemika Branch the Central JavaSample in this research is staff employees remain to PT. Brataco Semarang. Sum up the sample taken in research adapted for by a minimum condition of sample which must befulfilled in SEM. Sum up the sample as much 5 times sum up the indicator becoming minimum standard. Indicator in this re search is 21 indicator, so that minimize the sample which must be taken is 105 sample. Data wlziclz is in analysis comefrom spreading questioner to employees of taken as sample in this research.Result of this research indicate that the organizational climate have an effect on positive to satisfaction work the value C.R. equal to 4,423. Motivation have an effect on positive to satisfaction work the employees assess the C.R. equal to 2,964. Organizational climate have an effect on positive to employees peiformance assess the C.R. equal to 4,113. Motivation have an effect on positive to employees peifornzance assess the C.R. equal to 2,875. Satisfaction work to have an effect on positive to employees peifornzance assess the C.R. equal to 2, 736, meaning the value abovefar above 2,00, its meaning organizational climate excelsior, motivate and satisfaction work hence can improve the employees peifornzance Keywords: Employees Peiformance, Satisfaction work, Motivation, and Organizational Climate